2016
DOI: 10.1186/s12913-016-1522-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of e-health and m-health tools in health promotion and primary prevention among older adults: a systematic literature review

Abstract: BackgroundThe use of e-health and m-health technologies in health promotion and primary prevention among older people is largely unexplored. This study provides a systematic review of the evidence on the scope of the use of e-health and m-health tools in health promotion and primary prevention among older adults (age 50+).MethodsA systematic literature review was conducted in October 2015. The search for relevant publications was done in the search engine PubMed. The key inclusion criteria were: e-health and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
209
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(237 citation statements)
references
References 25 publications
9
209
0
19
Order By: Relevance
“…Our findings are consistent with the results from a previous systematic review of TBIs that showed that little studies monitored intervention dose (number of log on and website exploration) and its influence on HRQoL among breast and prostate cancer patients . Maintaining intervention use over time during study is a major moderator of TBI effectiveness and is likely to influence participants' long‐term health outcomes . In this review, participant retention rates between baseline and the end of follow‐up were considered high, ranging from 73 to 94% .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings are consistent with the results from a previous systematic review of TBIs that showed that little studies monitored intervention dose (number of log on and website exploration) and its influence on HRQoL among breast and prostate cancer patients . Maintaining intervention use over time during study is a major moderator of TBI effectiveness and is likely to influence participants' long‐term health outcomes . In this review, participant retention rates between baseline and the end of follow‐up were considered high, ranging from 73 to 94% .…”
Section: Discussionsupporting
confidence: 88%
“…Professional support in TBIs could provide information, guidance, and assistance for users regarding their symptoms management . The lack of guidance and assistance by health professionals is a substantial barrier to the use of TBIs among elderly people (eg, prostate cancer patients), while health care providers' guidance and assistance have resulted in more enhanced self‐management in patients with chronic conditions than TBI access alone . Similarly, Seiler and colleagues found in a systematic review that therapist‐guided TBIs were more efficacious than self‐guided interventions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of sustained and sufficient funding from stakeholders such as governing bodies e.g. the government [33] indirectly affect the quality of service that healthcare providers can provide to their patients. A further problem, agreeing on reimbursement [24], can be a challenge for new technologies especially as they are of unproven value [7] as well as when some technologies are initially viewed as too expensive to integrate into everyday clinical practice [31].…”
Section: Challengesmentioning
confidence: 99%
“…E-Health solutions are increasingly common in healthcare, and involve the use of an electronic device or monitoring system by individuals or their healthcare providers to monitor or improve their health status [1]. Well-designed e-Health solutions for diabetes management targeting health behaviour change can improve a range of measures, including improvements in glycemic control, perceived health, and a reduction in hospitalizations [2, 3].…”
Section: Introductionmentioning
confidence: 99%